Status and Challenges of Care in Africa for Adults With Congenital Heart Defects. (July 2017) - Edwin, Frank; Zühlke, Liesl; Farouk, Heba; Mocumbi, Ana Olga; Entsua-Mensah, Kow; Delsol-Gyan, Desrie; Bode-Thomas, Fidelia; Brooks, Andre; Cupido, Blanche; Tettey, Mark; Aniteye, Ernest; Tamatey, Martin M.; et al.
The 54 countries in Africa have an estimated total annual congenital heart defect (CHD) birth prevalence of 300, 486 cases. More than half (51.4%) of the continental birth prevalence occurs in only seven countries. Congenital heart disease remains primarily a pediatric health issue in Africa because of the deficient health-care systems: the adults with CHD made up just 10% of patients with CHD in Ghana, and 13.7% of patients with CHD presenting for surgery in Mozambique. With Africa's population projected to double in the next 35 years, the already deficient health systems for CHD care will suffer unbearable strain unless determined and courageous action is undertaken by the African leaders.